Perovskite and Organic Solar Cells Fabricated by Inkjet Printing: Progress and Prospects. (27th September 2017) - Peng, Xiaojin; Yuan, Jian; Shen, Shirley; Gao, Mei; Chesman, Anthony S. R.; Yin, Hong; Cheng, Jinshu; Zhang, Qi; Angmo, Dechan
Abstract: Inkjet printing (IJP) technology, adapted from home and office printing, has proven to be an essential research tool and industrial manufacturing technique in a wide range of printed electronic technologies, including optoelectronics. Its primary advantage over other deposition methods is the low‐cost and maskless on‐demand patterning, which offers unmatched freedom‐of‐design. Additional benefits include the efficient use of materials, contactless high‐resolution deposition, and scalability, enabling rapid translation of learning from small‐scale, laboratory‐based research into large‐scale industrial roll‐to‐roll manufacturing. In the development of organic solar cells (OSCs), IJP has enabled the printing of many of the multiple functional layers which comprise the complete cell as part of an additive printing scheme. Although IJP is only recently employed in perovskite solar cell (PeSC) fabrication, it is already showing great promise and is anticipated to find broader application with this class of materials. As OSCs and PeSCs share many common functional materials and device architectures, this review presents a progress report on the IJP of OSCs and PeSCs in order to facilitate knowledge transfer between the two technologies, with critical analyses of the challenges and opportunities also presented. Abstract : An environmentally friendly and scalable manufacturing method is essential for the successful commercialization of perovskite and organic solar cells. Inkjet printing is a roll‐to‐roll compatible technique which is demonstrated in lab to industrial scale production. Herein, the use of inkjet printing in perovskite and organic solar cells is reviewed together to facilitate knowledge exchange, as both technologies use similar materials and processes.